Arbitrator’s Authority to Decide Ex Aequo et Bono: A Juridical Review - Hadylaya, Michael Herdi (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2023)
Arbitration is a dynamic practice. One of the issues to consider is the implementation of ex aequo et bono by arbitrators, which many parties see as requiring prior approval from the parties so that arbitrators can make decisions based on ex aequo et bono. This study concludes that the arbitrator's authority to decide ex aequo et bono is not derived from the parties' agreement but rather from the arbitrator's inherent authority. First, because this principle is consistent with the spirit of arbitration, the Arbitrator has the authority to decide ex aequo et bono. Second, Law Number 48 Year 2009 concerning Judicial Authority imposes an obligation to investigate, adhere to, and comprehend legal values and the sense of justice in society. Third, no provision in Law Number 30 Year 1999 concerning Arbitration and Alternative Dispute Resolution requires the parties to agree in advance on the grant of ex aequo et bono.